JianPiYiShen formula prevents cisplatin-induced acute kidney injury in mice by improving necroptosis through MAPK pathway - Zhongtang Li; Riming He; Jiahui Liu; Xiaoming Jin; Beibei Jiang; Yunlan Lao; Shudong Yang (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Acute kidney injury (AKI), characterized by necroptosis and activation of MAPK pathway, causes sudden declines in renal function. To date, efficacious treatments are lacking. JianPiYiShen Formula (JPYSF) has a protective effect on the kidneys. The aim of this study is to explore the mechanism of JPYSF in cisplatin-induced AKI. Methods Male C57/BL6J mice were divided into control group, cisplatin group and cisplatin + JPYSF group. Before establishing the model, the cisplatin + JPYSF group was administered JPYSF (18.35 g/kg/day) by gavage for 5 consecutive days. A single intraperitoneal injection of cisplatin (20 mg/kg) was used to establish AKI model. Measurement of renal function and H&E staining were performed to assess renal damage. WB, PCR, TUNEL staining and immunohistochemistry were used to detect related indicators of mitochondrial function, oxidative stress, necroptosis, inflammation and MAPK pathway. And one-way analysis of variance was used to compare group differences. Results Compared with the cisplatin group, JPYSF can attenuate AKI, reflected by the decrease in Scr and BUN levels, the improvement of renal tubular injury, and the downregulation of NGAL and KIM1. Cisplatin can induce mitochondrial dysfunction and oxidative stress, triggering necroptosis. In this study, JPYSF improved mitochondrial dysfunction to enhance oxidative stress, as manifested by upregulation of OPA1, PGC-1α, SOD and CAT, and downregulation of DRP1 and MFF. Then JPYSF showed a significant protective effect in necroptosis, as embodied by reduced number of TUNEL-positive cells, decreased the gene expression of RIPK3 and MLKL, as well as downregulation the proteins expression of P-RIPK1, P-RIPK3, and P-MLKL. Moreover, necroptosis can aggravate inflammation. JPYSF ameliorated inflammation by improving inflammatory and anti-inflammatory indexes, including downregulation of TNF-α, IL-6, MCP-1 and LY6G, and upregulation of IL-10. In addition, JPYSF also inhibited MAPK pathway to improve necroptosis by decreasing the expression of P-JNK and P-ERK. Conclusion Our data showed that JPYSF prevents cisplatin-induced AKI by improving necroptosis through MAPK pathway, which is related to the improvement of mitochondrial dysfunction, oxidative stress, and inflammation.